Phenotypic variation in a neotropical understory bird driven by environmental change in an urbanizing Amazonian landscape - Avilla, Stefano Spiteri; Sieving, Kathryn E.; Anciães, Marina; Cornelius, Cintia (Oecologia, 2021)
Environmental change through habitat fragmentation and urbanization drives biodiversity loss in the Neotropics at an alarming rate. Some individuals and species confined to habitat fragments may develop phenotypic adjustments that allow populations to persist, even in landscapes made harsh by human activities. Behavioral and morphological adjustments may enhance a population’s ability to cope with anthropogenic hazards. We examined potential differences in the behavioral and morphological phenotype of populations of the neotropical Wedge-billed Woodcreeper (Glyphorynchus spirurus)—an understory forest specialist insectivorous bird—between populations from urban fragmented forests and continuous preserved forests. We evaluated exploratory behavior and morphological traits using generalized linear models and linear discriminant analysis to quantify phenotypical differences among populations. We used failure time analysis to compare latency to explore and move during exploration in a Novel Environment Test (NET). Our analyses detected differences in certain movement behaviors (latencies to move during NET), indicating that individuals from fragmented forests are slow explorers in relation to individuals from the continuous forest. We also found shorter tarsi and tails in the fragmented forest population which were attributed to an overall reduction in body size in these populations. Our results suggest that environmental change driven by fragmentation in an urban landscape is causing population differentiation, but we cannot ascribe observed variations to evolutionary processes only, as the differences observed may be explained by other processes too. However, we suggest that phenotypic differences may be aiding this small understory forest specialist to persist in an urban fragmented landscape. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Amazon; Forest bird; Fragmentation; Phenotypic variation